Comprehensive application analyses of elastic models and viscoelastic models in transient flows in polymeric pipelines. Issue 5 (6th September 2022) - Duan, Xiangyu; Zhu, Jianghui; Li, Xiaoqin; Tang, Xuelin
Abstract: Based on the MOC (Method of Characteristics), the applicabilities of both the elastic models of the SF (Steady Friction), the CB-UF (Convolution-Based Unsteady Friction) and the MIAB-UF (Modified Instantaneous Acceleration-Based UF), and the viscoelastic models of the SF-VE (SF-Viscoelasticity), the CB-UF-VE (Convolution-Based Unsteady Friction-Viscoelasticity) and the MIAB-UF-VE (Modified Instantaneous Acceleration-Based UF-Viscoelasticity), are investigated for hydraulic transients induced by a downstream rapid valve closure in a polymeric pipeline. The predicted results by the elastic models are very different from the experimental data, whereas the predicted pressure peaks and phases by the viscoelastic models agree well with the experimental data because considering the pipe–wall creep effect, the CB-UF-VE and the MIAB-UF-VE generate better results than the SF-VE. The creep effects near the first pressure peak are captured well by the viscoelastic models. The analyses of the contributions of different factors to pressure attenuation show that for transient flows in polymeric pipelines, the effect of VE is greater than that of the CB-UF and MIAB-UF. The spectrum analyses show that the pressure amplitudes and harmonic frequencies by the elastic models match badly with the experimental data, whereas those by the viscoelastic models match well with the experimental data. The harmonic frequencies by the MIAB-UF-VE are the best, followed by the CB-UF-VE, and are worst by the SF-VE. HIGHLIGHTS: The applicabilities of elastic models and viscoelastic models are investigated based on the MOC for the hydraulic transients in a viscoelastic pipe. The pressure peaks and phases are captured. The creep effects near the first pressure peak are captured. The effects of VE and UF on pressure attenuation are analyzed. The pressure amplitudes and harmonic frequencies by the viscoelastic models match well the experimental data. Graphical Abstract